Evaluasi Implementasi Program Sekolah Adiwiyata di Sekolah Dasar Swasta Nurcahaya Kota Medan - Fadilah Syam Rangkuti; Badaruddin Badaruddin; Robert Tua Siregar (Universitas Medan Area, 2022)
The purpose of this article is to evaluate the implementation of the Adiwiyata program which is devoted to the role of school residents at SDS Nurcahaya, Medan. And analyze how SDS Nurcahaya can maintain the Adiwiyata award at different levels, seen from the supporting and inhibiting factors they experience. The object of this research is the residents of the SDS Nurcahaya school which consists of the principal, teachers/teaching staff and students who are involved in the Adiwiyata team. The method used in this study is a qualitative descriptive/descriptive method. Data collection techniques were carried out by in-depth interviews, and collecting data sources as reading material from books, previous research and others. The results of the research conducted show that the role of school residents to implement environmental-based education is quite good. This is because all school members have participated as much as possible. Based on the criteria given by the DLH, SDS Nurcahaya managed to meet the predetermined standards. The conclusion that can be drawn from this research is that it is necessary to make strict regulations and sanctions for school residents who do not comply with the Adiwiyata program regulations that have been mutually agreed upon.